Grundlagenforschung zum Dualen System und Kompetenzentwicklung in der Lehrerbildung - Faßhauer, Uwe; Fürstenau, Bärbel; Wuttke, Eveline (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2011)
For some years now, vocational and business education-oriented teaching and learning research has been providing insights into the connection between specialist knowledge and competence development and developing specific methods for diagnosing action competence in vocational domains for which training is provided in Germany's dual vocational training system. This research methodological instrument is increasingly used with regard to the target group of educational personnel, above all teachers at vocational schools, especially in the first phase of their professionalisation. This volume also focuses on studies on the acquisition of competencies in various domains, on methods of measuring competency development and on didactic design. This always touches on the basic themes of the development of vocational action competence, which form the basis of the dual system, also in the analysis of consecutive forms of training. Finally, questions about the effects of demographic change are focused on the development possibilities of vocational schools, which in the coming years will undoubtedly be increasingly perceived and dealt with by vocational and business education research.